The Paths and Challenges of Bioethics from an African Perspective: A Leap towards an African Bioethics (Revista Iberoamericana de Bioética, 2019)
Today the African continent faces multiple challenges related to poverty, inequality and corruption which affect not only the quality of life, but also its educational and health systems. There is an urgent need to develop an ethics of life (African bioethics) in line with the social, political, economic and moral reality of the African continent. Without this work of contextualization, any reflection regarding the integral human development of the African populations would be hypothetical or unachievable.
Keywords: African bioethics; development aid; democracy; biotechnology; leap-frogging